2020
DOI: 10.3390/healthcare8020070
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Dermatitis and Comorbidity

Abstract: Atopic dermatitis is the most common chronic inflammatory skin disease. It is often the first indicator of allergic diseases, and a certain percentage of patients are affected by allergic rhinitis and/or asthma as a consequence. The study aimed to investigate the link between atopic dermatitis and comorbidity in family medicine. In the specialist family medicine practice Osijek, a retrospective study was conducted in the period from January 1, 2016 to July 1, 2017 on the percentage of patients with atopic derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
(60 reference statements)
1
11
0
1
Order By: Relevance
“…The prevalence of AD is constantly growing worldwide over the past 30 years, and nowadays, AD affects about 10% of adults and up to 20% of children [ 2 ]. AD is associated with multiple comorbid chronic disorders, such as asthma, allergic rhinitis, respiratory infection, mental disorders, metabolic syndrome, gastrointestinal problems, and cardiovascular disease [ 3 ]. A recent cohort study has revealed a variety of clinical forms of AD in adult-onset and childhood-onset types, which may be a crucial factor in determining the appropriate therapeutic medications [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of AD is constantly growing worldwide over the past 30 years, and nowadays, AD affects about 10% of adults and up to 20% of children [ 2 ]. AD is associated with multiple comorbid chronic disorders, such as asthma, allergic rhinitis, respiratory infection, mental disorders, metabolic syndrome, gastrointestinal problems, and cardiovascular disease [ 3 ]. A recent cohort study has revealed a variety of clinical forms of AD in adult-onset and childhood-onset types, which may be a crucial factor in determining the appropriate therapeutic medications [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the occurrence of rheumatoid arthritisin atopic patients is found to reduce the atopy symptoms by 40 to 50% affirming that regulation of Th1 and Th2 cells strongly influences the inflammatory responses and disease outcome [27] .The observations about the above discussed two diseases,rheumatoid arthritis (Th1 predominance) and atopy (Th2 predominance), verify the above concept of immunity patterns for COVID–19. Further, infections are a common comorbidity in long-term atopic dermatitis [28] . Patients suffering from chronic atopic dermatitis show increase in Th1.…”
Section: Resultsmentioning
confidence: 99%
“…Atopic dermatitis (AD) is the most widespread chronic inflammatory skin disease marked by pruritus and relapsing course [ 100 , 101 ]. It is also known as eczema and atopic eczema.…”
Section: Clinical Application Of Silvermentioning
confidence: 99%